Pengaruh Penerapan ISO140001 Tingkat Resiko dan Likuiditas terhadap Profitabilitas Perusahaan Jasa dan Perhotelan di BEI 2019-2023 - Fuji Nurdiani; Francis Hutabarat; Riky Sai Maruli (Jurnal Simki Economic, 2026)
This study seeks to examine the influence of ISO 14001 implementation, risk level, and liquidity on the profitability of service and hotel companies listed on the Indonesia Index (BII) Exchange during the 2019–2023 period. The research applies a quantitative approach using multiple linear regression analysis. Research variables include the implementation of ISO 14001, risk level (DER), liquidity (CR), and profitability (ROA). The research sample consisted of 90 observations over five years. The findings indicate that collectively the three independent variables do not significantly influence profitability, as shown by a significance value of 0.089 (> 0.05). Individually, each independent variable also demonstrates no significant effect on profitability. Furthermore, the R² value of 0.0725 suggests that the model explains only 7.25% of the variation in profitability. These findings indicate that profitability is more influenced by other external and operational factors outside the research model.